2014
DOI: 10.1103/physrevb.90.094206
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Ba-Ti-Al-O glasses produced by aerodynamic levitation and laser heating

Abstract: Ba 0.09 Al 0.18 Ti 0.12 O 0.61 glasses have been produced by aerodynamic levitation and laser heating. Neutron diffraction, x-ray diffraction, x-ray absorption spectroscopy, molecular dynamics simulation, and reverse Monte Carlo refinement methods have been used to obtain a detailed atomistic structural model of the glass. This model has been used to investigate its atomic coordination and network structure. It is found that the Al atoms are almost exclusively fourfold tetrahedrally coordinated to oxygen atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Figure 2 shows the partial structure factor weightings for neutron scattering experiments. In contrast to the X-ray case it can be seen that the weighting of 12 may be clearly noted and support the observation previously that the Morse potentials of Pedone et al [16] are better for these aluminate glass systems [17]. data.…”
Section: Simulation and Modelling Methodssupporting
confidence: 87%
See 2 more Smart Citations
“…Figure 2 shows the partial structure factor weightings for neutron scattering experiments. In contrast to the X-ray case it can be seen that the weighting of 12 may be clearly noted and support the observation previously that the Morse potentials of Pedone et al [16] are better for these aluminate glass systems [17]. data.…”
Section: Simulation and Modelling Methodssupporting
confidence: 87%
“…Previous studies[17] have suggested that the Morse potentials give a better initial agreement with the data than the Buckingham potentials.However, suitable Morse potentials forTb-O could not be found in the literature so we have used the Morse potentials of Pedone et al[16] for the…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The low-r cutoffs used in the refinement were obtained by reference to the MD simulation. In addition, real-space data [ nat G(r)] was included to avoid a "pileup" of bonds close to the cutoff distances, primarily in g CaO (r) [38]. The mean square displacement from the original atoms at the end of the Fig.…”
Section: Reverse Monte Carlo Structure Refinementmentioning
confidence: 99%
“…To the best of our knowledge, several techniques such as Reverse Monte Carlo (RMC) [9] and Empirical Potential Structural Refinement (EPSR) [10] have been recently developed to obtain structural models of glasses from diffraction data. An alternative approach to the gallate glasses is to use Molecular Dynamics (MD) simulation techniques [11,12] to produce distribution function or diffraction patterns that can be compared directly with the experimental data.…”
Section: Introductionmentioning
confidence: 99%